Where is menstruation in global health policy? The need for a collective understanding - Josie McAllister; Fran Amery; Melanie Channon; Jennifer Thomson (Global Public Health)
From both an academic and a policy angle, menstruation is receiving an unprecedented level of attention. Within the academic literature, there are many different normative arguments being furthered for how menstruation should be understood and framed – variously, that it should be understood as an issue of rights, justice, health or hygiene management. Yet less attention has been paid to the step preceding these normative arguments – how menstruation actually is understood at present within global health policy. In this paper, we argue that, despite this proliferation of academic and policy interest, attention to menstruation is still relatively muted at the level of global health policy. Using Carol Bacchi’s ‘what’s the problem?’ approach to critical frame analysis, we show that global health policy on menstruation remains patchy, with little cohesive understanding of it as a policy issue emerging at the international level. Instead, competing constructions of it as an issue emerge, such that there is not one clear way in which menstruation is addressed in international health policy. We sketch the implications of this, arguing that without a collective understanding of the problem, solutions are likely to remain siloed, and cross-sectoral work will be difficult.